Real-World Challenges and Multidimensional Pathways for Advancing Curriculum-Based Ideological and Political Education in Vocal Music Courses at Teacher-Training Universities in the New Era - Yu, Binhong (Journal of Research in Vocational Education, 2026)
The comprehensive advancement of curriculum-based ideological and political education constitutes a strategic measure for fulfilling the fundamental educational task of fostering virtue through education in China and an essential requirement for the high-quality development of higher education in the new era. As institutions responsible for preparing future teachers for basic education, teacher-training universities are expected, through vocal music instruction, not only to cultivate students’ professional competencies but also to shape their professional ethics and transmit cultural values. Yet current implementation still faces a range of challenges, including incomplete understandings of the concept, overly narrow entry points, and underdeveloped evaluation systems. Against the backdrop of emerging trends and new developments in educational research both in China and internationally, this paper examines the positioning and objectives of vocal music courses at teacher-training universities, analyzes the major difficulties confronting current practice, and systematically explores strategies for further advancing curriculum-based ideological and political education from the perspectives of conceptual renewal, pedagogical innovation, evaluation reform, and the construction of collaborative mechanisms. The study seeks to provide both theoretical support and practical pathways for building an educational framework that engages all personnel, spans the entire educational process, and operates across multiple dimensions.